DEVELOPMENT OF THE STOCK MARKET AND EMISSION ACTIVITY OF JOINT-STOCK COMPANIES IN UZBEKISTAN: TRENDS AND PROSPECTS - Dilnozakhon Mukhitdinova (European Science Publishing, 2025)
This scientific article presents a statistical analysis of the development of Uzbekistan's stock market and the share issuance activity of joint-stock companies from 2022 to 2025. The study examines the growth in the size of the stock market, the number and volume of initial public offerings (IPOs), and changes in investor activity. The results indicate that capital-raising activity in Uzbekistan's stock market increased markedly in 2023 – no IPOs were held in 2021–2022, whereas 3 IPOs took place in 2023. During this period, trading volume surged five-fold and market capitalization reached about 21% of GDP. However, the amount of capital raised via IPOs remains low; for instance, the February 2023 IPO of UzAuto Motors garnered only $5 million instead of the $90 million target. A comparative analysis with foreign experiences (e.g., the U.S. and China) suggests that further institutional reforms, enhanced foreign investor confidence, and incentives for new share issuances are needed to advance Uzbekistan’s capital market. Based on these findings, practical recommendations are proposed to boost stock market activity in Uzbekistan.
Keywords: Stock market, IPO, share issuance, joint-stock company, investor activity, statistics, capital market, comparative analysis, reforms, international experience.